Validation of the Schizophrenia Quality of Life Scale Revision 4 (SQLS-R4) Among Patients with Schizophrenia - Isjanovski, Viktor (Open Access Maced J Med Sci, 2016)
BACKGROUND: The main goal of psychiatric care is not to be focused only on reducing psychopathological symptoms, but on improvement of the patient’s quality of life. AIM: To examine validation and reliability SQLS-R4 among patients with schizophrenia. METHODS: The sample consisted of 61 outpatients with schizophrenia attending the Psychiatry Hospital “Skopje”. nclusion criteria for subject selection were: 1) age more than 18 years, 2) clinically stable (not acutely ill or has not been recently hospitalized at least for the past 3 months). They completed SQLS-R4 and SF36 questioners. RESULTS: The internal consistency reliability was satisfactory for both the psychosocial and vitality domains (Cronbach’s α = 0.928, 0.83). Most of the items were significantly correlated with own scale score (from 0.189 to 0.687). The average of the score for the psychosocial quality life was 39.9 ± 8.6 (sometimes), for the cognition and vitality was 26.5 ± 6.1 (sometimes) (SQLS-R4). There was moderate correlation between SF 36-energy with SQOLS - motivation and energy; SF 36-mental health correlation with SQOLS-psychosocial. CONCLUSION: SQLS-R4 appears to offer excellent potential as an easily administered and patient acceptable assessment and monitoring measure of quality of life (QoL). However, a principle psychometric criterion crucial to the use and validity of the instrument concerns the underlying factor structure.